ATTITUDE CONTROL SYSTEM DESIGN FOR A RIGID-FLEXIBLE SATELLITE USING THE H-INFINITY METHOD WITH PARAMETRIC UNCERTAINTY - Souza, Alain Giacobini de; Souza, Luiz Carlos Gadelha de (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents the Attitude Control System (ACS) design for a rigid-flexible satellite with two vibrations mode, using the H infinity method considering the parametric uncertainty over the mass matrix. Usually the mathematic model obtained from the linearization and/or reduction of the rigid flexible model loses information about the flexible dynamical behavior and introduces some uncertainty. As a result, the ACS performance can be degraded when controlling large angle maneuvers. One way to recovery the dynamics information is to include in the ACS design the parametric and not parametric uncertainties of the system. The rigid flexible satellite dynamics can be represented by an ordinary differential equation (EDO), which coefficients are the matrices mass, damping and rigidly. In this paper one investigates the influence of the uncertainty in the mass matrix in the control law performance designed by the H infinity control methodology. The results of the simulations have shown that the control law designed using the H-infinity control method considering the parametric uncertainty is robust since the ACS performance has been improved in controlling the rigid flexible satellite attitude and suppressing vibrations. Keywords: ACS, Satellite rigid-flexible, Uncertain, H infinity